Manajemen dan Tata Kelola Energi Listrik di Pondok Pesantren Sa’adatuddaren Kelurahan Tahtul Yaman Kecamatan Pelayangan Kota Jambi - Nazarudin, Muhammad Haviz, Oki Alfernando, Ira Galih Prabasari, Ulyarti (ANDAN JEJAMA: Indonesian Journal of Community Engagement (IJCE), 2022)
Electricity has become a basic need which people depend on as an energy source for their electrical equipment. It can increase their monthly expenditure if they can not manage how to use it efficiently based on electrical usage and safety standards. According our preliminary survey, we found that in The Pesantren (islamic boarding school) of Sa'adatudaren at Urban Village of Tahtul Yaman in Sub-district of Pelayangan, City of Jambi, electrical utilities in this Pesantren have not yet operated using minimal electrical usage standards so it was not safe and the same time increased their monthly expenditure. In this community service activity, we trained the students, the teachers and the management of the Pesantren of Sa'adatudaren how to use electricity efficiently using electrical safety standards and electrical management systems. At the end of training, we distributed some stickers and banners to be spread around the Pesantren.